MANAGING SCHOOL LITERACY PROGRAMS IN PUBLIC SENIOR HIGH SCHOOLS IN AMBON - Dina; Patrisius Rahabav; Paul Arjanto (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study describes and analyzes the management of school literacy programs at SMA Negeri 9 Ambon and SMA Negeri 5 Ambon. The research used a qualitative multi-site design because it examined naturally occurring school practices in two senior high schools. Data were collected through observation, semi-structured interviews, and documentation involving principals, teachers, library staff, and students. The analysis followed the interactive model of data reduction, data display, and conclusion drawing, while credibility was strengthened through source, technique, and time triangulation. The findings show that the two schools have implemented literacy activities, especially reading before lessons, but the level of management varies. At SMA Negeri 5 Ambon, planning reached 75%, organizing 100%, implementation 100%, and evaluation 100%. The school also conducts an annual Language Month program to develop students' literacy interests. At SMA Negeri 9 Ambon, planning reached 50%, organizing 66.6%, implementation 100%, and evaluation 66.6%. Both schools have not yet established a formal School Literacy Team, and several activities remain dependent on subject teachers. Supporting factors include principal support, teacher involvement, library availability, and coordination between teachers and library staff. Inhibiting factors include limited varied reading materials, low student reading motivation, teacher punctuality issues, and the absence of formal evaluation instruments. The study concludes that literacy programs require stronger formal planning, structured teams, diversified reading resources, and systematic evaluation to become sustainable school culture.